The impact of working capital management on profitability performance on public listed companies in Malaysian market / Norsyahira Muhamed Shah - Muhamed Shah, Norsyahira (Bachelor of Business Administration (Hons) Marketing, 2015)
Companies can use working capital management as an approach to influence their profitability. This paper studies the impact of working capital management and its components upon the profitability of public listed companies in Malaysian market. In this research, a sample of 93 public listed companies in Bursa Saham were selected for a period of 3 years from 2012 – 2014. This research have studied the effect of different variables of working capital management including the average collection period (ACP), inventories turnover (ITO), average payment periods (APP), cash conversion cycle (CCC), current asset to total asset ratio (CATAR) and current liabilities to total asset ratio (CLTAR) towards the return on asset (ROA). The data was analysed through the regression analysis to find out the impact of working capital management on profitability. Then, correlation analysis was used to find out the relationship between working capital management with profitability. Based on the findings, the results show that there is a significant negative relationship between ACP and CLTAR with ROA, then, a significant positive relationship with CATAR and ROA. The other variables which are APP, ITO and CCC have insignificant negative relationship with ROA